2019
DOI: 10.1158/1055-9965.epi-18-0965
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and Non-Aspirin NSAID Use and Prostate Cancer Incidence, Mortality, and Case Fatality in the Atherosclerosis Risk in Communities Study

Abstract: Background: NSAIDs appear to moderately reduce prostate cancer risk. However, evidence is limited on whether NSAIDs protect against prostate cancer mortality (death from prostate cancer among men without a cancer history) and case fatality (death from prostate cancer among men with prostate cancer), and whether benefits are consistent in white and black men. This study investigated associations of aspirin and non-aspirin (NA) NSAID use with prostate cancer incidence, mortality, and case fatality in a populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
4
19
0
Order By: Relevance
“…These studies supported the protective influence of aspirin on PC patients and delayed the progression of PC. Hurwitz et al recently discovered that aspirin use was inversely associated with the risk of PCSM [12]. However, they found that aspirin did not effectively reduce the incidence of PC.…”
Section: Discussionmentioning
confidence: 99%
“…These studies supported the protective influence of aspirin on PC patients and delayed the progression of PC. Hurwitz et al recently discovered that aspirin use was inversely associated with the risk of PCSM [12]. However, they found that aspirin did not effectively reduce the incidence of PC.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, data prospectively obtained in the Southern Community Cohort Study suggested that aspirin use is tentatively associated with a reduced prostate cancer mortality in African American men [127]. Hurwitz et al also observed this inverse relationship between aspirin use and prostate cancer mortality in both African American and European American men using the ARIC cohort [128], again pointing to the potential benefit of aspirin use for men at high risk of fatal prostate cancer.…”
Section: Anti-inflammatory Drug Aspirin For Prevention Of Adverse Outcomes In African American Men With Prostate Cancermentioning
confidence: 95%
“…In addition to the 4 representative therapeutic effects already mentioned, a low dose of ASA has been used for reducing the risk of heart attack and stroke [14]. Long-term medication for at least 10-20 years may be effective in cancer prevention, especially with colorectal cancer [15], but also with endometrial [16], breast [17], and prostate cancer [18].…”
Section: ① Nsaidsmentioning
confidence: 99%